Child support beyond marriage in Islamic law: Revisiting Ibn Taimiyah’s perspective - Nurasiah, Nurasiah; Tanti, Cek; Nurheliza, Siti; Ce Musa, Norsuhaida binti (UIN Ar-Raniry Banda Aceh, 2026)
This study explores the obligation of biological fathers to provide financial support for children born outside marriage, focusing on the groundbreaking views of classical jurist Ibn Taimiyah and their relevance to the modern law of child rights adopted in Indonesia. Traditional fiqh generally denies all civil rights of illegitimate children, such as maintenance, inheritance, or guardianship, assigning responsibility for their welfare to the mother or the state. Ibn Taimiyah, however, challenges this consensus by proposing a recognition mechanism (istilhaq) that can establish a paternal bond under specific conditions, with which a certain kind of child support can be imposed on the biological father. Using a juridical-normative approach, this research draws on Ibn Taimiyah’s writings and classical fiqh texts as primary sources, while contemporary journals in Islamic family law and Indonesian legislation are secondary. The findings reveal that Ibn Taimiyah’s concept should be considered progressive, aligns with maqāṣid al-sharī‘ah, and emphasizing the protection of children’s socio-economic rights, lineage, and welfare. His ideas resonate with modern legal developments in Indonesia, including the Constitutional Court Decision No. 46/PUU-VIII/2010 and MUI Fatwa No. 11/2012. This study argues that integrating Ibn Taimiyah’s insights can contribute to a more equitable and child-centered framework in contemporary Islamic family law.